Reputation, stock price, and you : why the market rewards some companies and punishes others - Kossovsky, Nir (Apress ; Distributed to the Book trade worldwide by Springer-Verlag, 2012)
?All of our working lives we have heard the mantra, 'a reputation lost is never regained.' Still, the firms we work for, admire and invest in seem to take costly reputation hits all too often. Everyone interested in managing, regulating or investing in public firms will find Nir Kossovsky's book a wonderful read through reputations won, lost and regained over the last 20 years. This is the first book which goes beyond platitudes to explain how to spot value-destroying reputation risk and how to manage it or live with its consequences. Couldn't be more timely.? --Tom Skwarek, Managing Director.